936 - Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: dept.hms

Marathon and ultra-endurance performance - Lunn, William R. (Medicine & Science in Sports & Exercise, 2023)
Keywords: dept.hms; peer-reviewed

Body Composition Evaluation During The Competitive Season Of An NCAA Division II Men's Soccer Team - Lunn, William; Axtell, Robert (Medicine & Science in Sports & Exercise, 2025)
Keywords: Athletes; Body fat percentage; Competitive athletes; Composition (language); Division (mathematics); Fat mass; Lean body mass; Team sport; dept.hms

Effect Of Creatine Monohydrate Supplementation On VO2 Kinetics In Aerobically Fit Adults - Raymond, Emerson; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Blood lactate; Creatine; Crossover study; Heart rate; Lactate threshold; Percentile; Treadmill; VO2 max; Ventilatory threshold; dept.hms

Similar Relative Energy Deficiency In Sport (REDs) Variables In Men And Women NCAA Distance Runners - Bryan, J.; Rupp, Kristie; Lunn, William (Medicine & Science in Sports & Exercise, 2025)
Keywords: Basal metabolic rate; Bone mineral; Doubly labeled water; Dual energy; Energy expenditure; Energy metabolism; Fat free mass; Fat mass; Physical activity; dept.hms

Cannabidiol supplementation alleviates anxiety, mitigates pain, extends endurance, and facilitates greater exercise exertion: 277 - Lunn, William R.; Axtell, Robert S. III; Venard, Anna; Bodurtha, Phillip; Brunello, Greta; Bukowski, Zachary (Medicine & Science in Sports & Exercise, 2023)
An abstract is unavailable.
Keywords: dept.hms; peer-reviewed

The effect of high dose creatine supplementation on thermoregulatory adaptation during a standard heat acclimation protocol - Martin, David; Thornton, Staci; Langan, Seam; Navarro, John; Brewer, Gabrielle; Szymanski, Michael; Huggins, Robert; Lunn, William; Rodriguez, Nancy; Casa, Douglas; Lee, Elaine (Medicine & Science in Sports & Exercise, 2025)
Keywords: Acclimatization; Analysis of variance; Core temperature; Creatine; Dehydration; Heat stress; Rectal temperature; Thermoregulation; dept.hms